Natural Justice, Procedural Justice, and the Judge’s Role in the Pancasila-Based Rule of Law - Susilo, Erwin (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2025)
This paper explores the relationship between natural justice and procedural justice, as well as its implications for the role of judges within the Pancasila-based rule of law. Procedural justice is often misconstrued as mere compliance with formal rules, even though it essentially represents an embodiment of natural justice principles that require judicial proceedings to be fair, impartial, and transparent. Employing normative legal research with a conceptual and statutory approach, this study examines core principles of natural justice, including audi alteram partem, nemo judex in causa sua, and the obligation to provide reasoned judicial decisions. These principles are integral to procedural justice and constitute a constitutional mandate as enshrined in Article 28D paragraph (1) of the 1945 Constitution. In relation to Pancasila, judges bear a professional and moral responsibility to ensure that procedural justice is upheld as the foundation of fair trials and the legal protection of every citizen.